Nuclear cultures - Nayar, Pramod K., author.
1 online resource (xii, 198 pages)
Keywords: "Nuclear Cultures: Irradiated Subjects, Aesthetics and Planetary Precarity aims to develop the field of nuclear humanities and the powerful ability of literary and cultural representations of science and catastrophe to shape the meaning of historic events. Examining multiple discourses and textual materials, including fiction, poetry, biographies, comics, paintings, documentary, and photography, this volume will illuminate the cultural, ecological and social impact of nuclearization narratives. Furthermore, this text explores themes such as the cultures of atomic scientists, the making of the bomb, nuclear bombings and disasters, nuclear aesthetics and art, and the global mobilization against nuclearization. Nuclear Cultures breaks new ground in the debates on "the nuclear" to foster the development of nuclear humanities, its vocabulary and methodology"--